Effects of probiotic on the intestinal morphology with special reference to the growth of broilers. - Lutfullah, Ghosia; Akhtar, Tasleem; Ahmad, Irshad; Khattak, Muhammad Muzaffar Ali Khan; Durrani, Fazal-E-Raziq; Qureshi, Muhammad Subhan (International Center for Chemical and Biological Sciences, University of Karachi, 2011)
The probiotic (Protexin)® increases the growth rate in broilers. It must interfere with the intestinal cell morphology and absorption. The intestinal epithelium is one of the most rapidly renewed tissues in the body and is renewed by a process of continuous cell division. This study was carried out with an aim to establish a link between the use of probiotic doses, growth rate, and intestinal cell proliferation by measuring the length and weight of the intestine and intestinal crypt cell proliferation (CCP) of broiler chicks. The results revealed significant increase in intestinal CCP but no effect was observed on the intestinal weight and length. The increase in CCP has also no significant influence towards growth factor. The increased weight gain in this study is associated with more feed consumption which is observed with Protexin® dose 1.0 g / 10 kg of feed. Furthermore, feed consumption reduced beyond this dose may lead to reduced weight gain.